2017
DOI: 10.1007/s10195-017-0451-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative outcomes and complications of suspensory loop fixation device versus hook plate in acute unstable acromioclavicular joint dislocation: a systematic review and meta-analysis

Abstract: Background Treatment of acute (B3 weeks) acromioclavicular joint dislocation type III-VI is still controversial. Currently, the two modern techniques that are widely used are hook plate (HP) fixation and coracoclavicular ligament fixation using a suspensory loop device that consists of either a tightrope (single or double), endo-button (single or double), or synthetic ligament and absorbable polydioxansulfate sling. Materials and methods This systematic review was conducted according to the PRISMA guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 55 publications
11
84
1
Order By: Relevance
“…Mean time from injury to surgery was 6.8 ± 3.8 days (range, 2-14). The mean time to return to work was 11.2 ± 2.9 weeks (range, [8][9][10][11][12][13][14][15][16][17][18][19][20]. When trauma mechanisms are examined, 15 patients were injured while doing sports, 14 patients were injured after a traffic accident, 5 patients were injured after falling from height and 2 patients were injured during a fight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean time from injury to surgery was 6.8 ± 3.8 days (range, 2-14). The mean time to return to work was 11.2 ± 2.9 weeks (range, [8][9][10][11][12][13][14][15][16][17][18][19][20]. When trauma mechanisms are examined, 15 patients were injured while doing sports, 14 patients were injured after a traffic accident, 5 patients were injured after falling from height and 2 patients were injured during a fight.…”
Section: Resultsmentioning
confidence: 99%
“…In this procedure, the CC ligaments are expected to heal since the AC joint is kept reduced and the AC and CC ligament remnants are brought into contact. In a systemic meta-analysis, loop fixation devices were found to have higher shoulder function scores and lower postoperative pain [14]. Another study comparing the results of loop button fixation and Bosworth screw fixation showed that more treatment satisfaction is achieved with loop fixation [15].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the optimal surgical technique for ACJ dislocation is still under debate owing to controversy in reported outcomes. In a recent study, hook plate xation was reported to be a popular option that provides rigid xation and promotes nature scaring of the CC ligament, with the advantages of a simpler surgical technique, minimally-invasive access, and early resumption of normal activity [4,[7][8][9]. Despite these advantages, hook plate xation also has disadvantages, which include the need for implant removal surgery, subacromial impingement, subacromial osteolysis, and possible loss of reduction after implant removal, which may lead to complications such as a rotator cuff tear or an acromion fracture in patients with osteoporosis or those with a high activity level [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic outcome * A p value of <0.05 was considered to be statistically signi cantDiscussionThe principal nding of the present comparative study was that concomitant CC reconstruction with hook plate xation provided a superior reduction maintenance and reduced the incidence of acromial osteolysis as compared with hook plate xation alone in acute high-grade ACJ dislocations, although there was no signi cant difference in the functional outcome. In recent decades, hook plate xation has become a popular option owing to the lesser requirement for dissection and simple application, allowing early shoulder girdle exercise, and with probably the same or a lower complication rate as compared with conventional pinning techniques[7,8]. Several studies have reported satisfactory functional outcomes of hook plate xation.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] When examining an AC joint dislocation, careful attention must be paid to skin conditions, infections or neurovascular issues. During postoperative care, pain management, recovery ability, and return to play are important issue both for the physician and patient, as well as recurrence of dislocation and the need of second surgeries to remove osteosynthesis material.…”
mentioning
confidence: 99%